Assessing the economic impact of droughts in Europe in a changing climate: A multi-sectoral analysis at regional scale - Corrado Motta; Gustavo Naumann; Diego Gomez; Giuseppe Formetta; Luc Feyen (Journal of Hydrology: Regional Studies)
Study region: The EU member states plus UK, Norway, and Switzerland. Study Focus: In the recent past, Europe has faced several extreme drought events that have generated high economic losses across socioeconomic sectors. Climate change is expected to alter the frequency and intensity of these events. In order to increase drought resilience through adaptation it is essential to discern regional and sectoral drought risk patterns that account for the specific characteristics of local territories. In this study, we integrate drought hazard modelling with regional exposure mapping and vulnerability assessment to quantify drought impacts in drought-sensitive sectors across 1366 administrative territorial units of Europe, considering present climate conditions and a range of global warming levels. New hydrological insights for the region: Our results show a strong regional disparity in future drought impacts, with an overall increase in drought losses in southern, south-eastern, and western regions of Europe and a decrease in northern regions. Regional differences are amplified with increasing global warming and depend on the intensity of the drought, modulated by the exposure and vulnerability of drought-sensitive socioeconomic sectors. In some of the most impacted regions, economic losses could become substantial, with expected annual losses corresponding to 1–2 % of regional gross domestic product, while the agriculture sector could lose 15 % of its gross value added with high levels of global warming.